Agricultural policies in Vietnam: producer support estimates, 1986-2002 - Nguyen, Hoa; Grote, Ulrike (International Food Policy Research Institute, 2004)
Since 1986, Vietnam started to move from a centrally-planned towards a market-oriented system. It underwent several major economic and trade reforms – a process which is still not completed. At the same time, it also started to open its economy. Vietnam has become a member of the ASEAN Free Trade Agreement (AFTA), signed several bilateral trade agreements and is currently negotiating accession to the World Trade Organization (WTO). First positive results of the reform process became visible in the early 1990s when poverty declined to a large extent. Since then, the Vietnamese agricultural sector has also experienced high growth and impressive export achievements. The country changed from a food importer to one of the major exporters worldwide. The question arises to what extent support policies contributed to this growth, especially of the agricultural sector. In order to answer this question, domestic and trade policies in the agricultural sector are analysed and the market price support (MPS) and producer support estimates (PSEs) are calculated. To account for the special conditions in Vietnam, the MPS and PSEs are adjusted for country- and commodity-specific factors like transportation costs, marketing margins and the quality difference of exportables (or importables) at the border and domestically. The selected agricultural commodities for which the MPS and PSEs are estimated include rice, coffee, tea, rubber, pepper, sugar, groundnut, cashew nut and pig meat. These nine commodities are the main agricultural products and exportables of Vietnam. Their shares in total output exceed 70% allowing for a generalization of the calculated PSEs, thus roughly representing the whole agricultural sector. The finding is that most agricultural products were taxed in the mid 1980s until the mid 1990s. This was often due to large inefficiencies in the production and processing of agricultural commodities, the dominance and monopoly position of the state-owned sector, restrictive trade policies like import and export quotas and licenses, and distorted markets and prices in the country. The domestic reform process, the opening of the economy since the early 1990s, and the shift from an import-substitution strategy towards export-promotion, however, impacted on the gaps between the domestic and international prices. Thus, since the mid 1990s, the support of agriculture increased - but still reaching only rather low levels. At its peak, the %PSE for the agricultural sector was 24.2% which is moderate compared with other countries. The low level of protection implies that Vietnam may not face excessive difficulties in its further international integration. This study of Vietnam is the third comprehensive review conducted within an IFPRI project on understanding and assessing domestic and trade policies in the agricultural sector in developing countries. The data are meant to deliver a basis for further trade-related research to be conducted in the future.